Consulta prévia no Estado do Pará: um estudo sob a perspectiva interdisciplinar da participação - MENDONÇA, Ygor de Siqueira Mendes (Universidade Federal do Pará, 2019)
The historical process in favor of the rights of traditional peoples and communities runs from the period of the Industrial Revolution to the current hierarchical relations of power in society. In this context, the creation of Convention 169 (C169) of the International Labour Organization (ILO) aimed to break the integrationist character of these humanitarian groups into national society and to promote, above all, the autonomy and self-determination of its subjects. By establishing the right to the Free, Prior and Informed Consent (FPIC) whenever administrative or legislative laws affect their way of life, development and subsistence, C169 has also sought to ensure the full participation of these actors in making decisions, especially through intercultural dialogue and communicative actions among those interested in the construction of laws. However, because of the existing regulatory shortcomings in the immediate effects and the means by which the consultation has been realized, the paths traced to the present moment are directed at the ineffectiveness in guarantee the traditional communities rights. For this reason, it is incumbent upon governments to promote adequate instruments to guarantee consultation and legitimize participation, to focus on participation itself, which limits consultation to a mere space for the exchange of information and limits the hierarchical power. Thus, in order to resolve the obstacles of the Free and Informed Consent in a regional context, the state government of Pará promulgated Executive Decrees 1.969/2018 and 2.061/2018. The result of the state's conduct came with the strengthening of the selfenforceability of FPIC's right, which opposed to an explicit violation of the right to participate. Thus, and in view of the need to promote an up-to-date look at the Free and Informed Consent right, it is the general objective of this dissertation to analyze government conduct in contraposition to the right to FPIC, specially participation. Therefore, from an interdisciplinary approach, the methodological procedures are based on a research of a qualitative nature and constructed through the hypothetical-deductive method. The research procedure adopted was the study case and the research techniques were focused on the collection of documentary, bibliographic data and interviews with two representatives of traditional communities of Para. From this methodological structure, it was possible to conclude by the misguided and contradictory conduct of the Para government, that the violation of the C169 proved to be uncontroversial, especially in light of the prior and proper participation. In addition, it was concluded that, as an alternative to attempts to regulate the right of Free and Informed Consent, the Consultative Protocols have gained space and normative force as an instrument of empowerment and self-government of traditional peoples and communities, in order to allow the formalization of their respective aspirations, worldviews and internal demands. In this direction, it is incumbent upon the State to promote awareness, feasibility and, above all, the full effectiveness of these instruments, as well as the creation of effective participatory spaces that consolidate the growth of ascendant power beyond the requirement of consent or attempts in their standardization.